2006
DOI: 10.1097/01.pai.0000210419.45869.79
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Histologic Features of Primary Breast Carcinomas and Axillary Lymph Node Micrometastases: Detection and Prognostic Significance

Abstract: The incidence and prognostic significance of micrometastases (Mic-Met) in axillary lymph nodes (LNs) is still controversial. We compared Mic-Met detection of invasive mammary carcinomas (IMCs) in axillary LNs using second review of hematoxylin and eosin (H&E)-stained slides and immunohistochemistry (IHC) relating them with features of the primary tumor, and determining their influence on overall survival (OS) and disease-free survival (DFS). We studied 188 cases of IMCs with no axillary metastases in the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 21 publications
0
30
0
2
Order By: Relevance
“…[13] McGuckin et al found lymph node metastases detection rate of 35% in cases with tumor size >2 cm as compared with 20% in cases with tumor size ≤2 cm and obtained a statistically significant correlation between tumor size and lymph node metastases detected by IHC. [3] In a study by Cote et al, 26% of the cases with tumor size >2 cm were positive for lymph node metastases detected by IHC as compared with 16% of the cases with tumor size ≤2 cm positive for lymph node metastases Wells et al [7] 1984 CK, EMA 15 Trojani et al [8] 1987 CK, EMA, HMFG1,HMGF2, AUA1 14 Berry et al [9] 1988 HMFG1, HMFG2, E29,CAM 5.2 17.3 Sedmak et al [10] 1989 CK AE1/AE3 14.4 Raymond and Leong [6] 1989 CK 23 Springall et al [11] 1990 CAM 5.2, HMFG2 20 Mascarel et al [4] 1992 CK, EMA,HMFG1, HMGF2, AUA1 22.9 Hainsworth et al [12] 1993 BC2, BC3, 3E1.2 12 Nasser et al [13] 1993 CK AE1/AE3, CAM 5.2 14 Cote et al [2] 1999 CK AE1, CAM 5.2 20 Umekita et al [14] 2002 CK AE1/AE3 14.2 de Mascarel et al [15] 2002 CK, EMA, HMFG1, HMFG2, AUAI 10 (IDC) and 41 (ILC) Lara et al [16] 2003 CK AE1/AE3, CAM 5.2 13 El-Tamer et al [17] 2005 CK (AE1/AE3 and KL1) 6 Broekhuizen et al [18] 2006 CAM 5.2 11 Marinho et al [19] 2006 CK AE1/AE3 12.2…”
Section: Discussionmentioning
confidence: 96%
“…[13] McGuckin et al found lymph node metastases detection rate of 35% in cases with tumor size >2 cm as compared with 20% in cases with tumor size ≤2 cm and obtained a statistically significant correlation between tumor size and lymph node metastases detected by IHC. [3] In a study by Cote et al, 26% of the cases with tumor size >2 cm were positive for lymph node metastases detected by IHC as compared with 16% of the cases with tumor size ≤2 cm positive for lymph node metastases Wells et al [7] 1984 CK, EMA 15 Trojani et al [8] 1987 CK, EMA, HMFG1,HMGF2, AUA1 14 Berry et al [9] 1988 HMFG1, HMFG2, E29,CAM 5.2 17.3 Sedmak et al [10] 1989 CK AE1/AE3 14.4 Raymond and Leong [6] 1989 CK 23 Springall et al [11] 1990 CAM 5.2, HMFG2 20 Mascarel et al [4] 1992 CK, EMA,HMFG1, HMGF2, AUA1 22.9 Hainsworth et al [12] 1993 BC2, BC3, 3E1.2 12 Nasser et al [13] 1993 CK AE1/AE3, CAM 5.2 14 Cote et al [2] 1999 CK AE1, CAM 5.2 20 Umekita et al [14] 2002 CK AE1/AE3 14.2 de Mascarel et al [15] 2002 CK, EMA, HMFG1, HMFG2, AUAI 10 (IDC) and 41 (ILC) Lara et al [16] 2003 CK AE1/AE3, CAM 5.2 13 El-Tamer et al [17] 2005 CK (AE1/AE3 and KL1) 6 Broekhuizen et al [18] 2006 CAM 5.2 11 Marinho et al [19] 2006 CK AE1/AE3 12.2…”
Section: Discussionmentioning
confidence: 96%
“…Some defined micrometastasis as metastatic tumor cells not detectable on routine histologic examination, whereas others (24-27) considered metastatic tumor cells by size into "micrometastases" (measuring > 0.2 mm) and "isolated tumor cells" (measuring ≤ 0.2 mm), as recommended by the sixth edition of the TNM classification of malignant tumors by UICC (16). Our definition of micrometastasis was the presence of tumor cells in regional lymph nodes not detected on routine H&E staining and we divided the metastasis into single-cell and cluster types in light of previous suggestions that this differentiation may be important (24-27).…”
Section: Discussionmentioning
confidence: 99%
“…Em 13/137 casos (9,5%), identificou-se a presença de células epiteliais metastáticas, tanto micrometástases (com dimensão entre 0,2 a 2 mm) como células tumorais isoladas (dimensão < 0,2 mm). A literatura relata taxas de detecção de micrometástases em 7% a 42% em linfonodos axilares, dependendo do método de estudo empregado (25)(26)(27)45) . Sabe-se que aproximadamente 25% dos pacientes linfonodo-negativos desenvolverão recidiva da doença e que poderiam talvez ter se beneficiado de quimioterapia adjuvante.…”
Section: Discussionunclassified